Development of Complexity, Accuracy, and Fluency in High School Students’ Written Foreign Language Production - Bouchaib Benzehaf (JEELS (Journal of English Education and Linguistics Studies), 2016)
The present study aims to longitudinally depict the dynamic and interactive development of Complexity, Accuracy, and Fluency (CAF) in multilingual learners’ L2 and L3 writing. The data sources include free writing tasks written in L2 French and L3 English by 45 high school participants over a period of four semesters. CAF dimensions are measured using a variation of Hunt’s T-units (1964). Analysis of the quantitative data obtained suggests that CAF measures develop differently for learners’ L2 French and L3 English. They increase more persistently in L3 English, and they display the characteristics of a dynamic, non-linear system characterized by ups and downs particularly in L2 French. In light of the results, we suggest more and denser longitudinal data to explore the nature of interactions between these dimensions in foreign language development, particularly at the individual level.